How can pictorial representations stimulate the imaginative capacity of experienced multimedia designers?. Issue 3 (3rd July 2019) - Liang, Chao-Tung; Chang, Yuhsuan; Liang, Chaoyun
Abstract: Designers value imaginative capacity and consider it the basis for cultivating creative ideas, but research on designer imagination is scant. Prior research has indicated that pictorial representations stimulate designers to imagine how their designs look or feel when they are used. Therefore, the present study explored the types of pictorial representation that stimulate the imaginative capacity of experienced multimedia designers as well as how this is achieved. This study conducted a series of in-depth interviews focusing on 10 indicators of imaginative capacity with 20 experienced multimedia designers. The results indicate that each indicator of imaginative capacity can be stimulated by various types or combinations of pictorial representation. How these stimulations occur largely depends on design problems and needs. The potential changes in design resulting from referring to pictorial representations were considered on the basis of five facets: optimal combination, presentation intentions, user experience, client needs, and resource availability. Resource availability was identified as a key determinant of final decisions made by experienced designers.